Sperm DNA fragmentation index does not correlate with blastocyst euploidy rate in egg donor cycles. (4th March 2018) - Gat, Itai; Li, Nancy; Yasovich, Natalia; Antes, Ran; Kuznyetsov, Valeriy; Zohni, Khaled; Weizman, Noga Fuchs; Librach, Clifford
Abstract: Sperm DNA fragmentation is a known etiology for male infertility. We evaluated the impact of sperm DNA fragmentation index (DFI) on blastocyst euploidy in IVF cycles with egg donors. This observational retrospective study, which was conducted in a university affiliated fertility clinic, included IVF-ICSI-pre-implantation Genetic Screening (PGS) egg donor cycles in which DFI was tested prior to IVF, between January 1st, 2014 and July 31st, 2016. Twenty-seven cycles with DFI > 15% were included in the study group and compared with 18 cycles of DFI < 15% within control group. Research group participants had significantly lower sperm count and motility (55.4*10 6 /ml and 37.4%, respectively) compared with controls (92.5*10 6 /ml and 55.7%, respectively, p < .05). The groups were similar in terms of donors' demography (age, BMI), ovarian reserve (AMH, AFC) and response to hormonal stimulation (E2 level on triggering day and number of retrieved eggs). Embryo development (from 2PN through day 3 embryos to blastocysts) was similar as well. The number of biopsied blastocysts from study and control groups was 171 and 87, respectively. PGS with array comprehensive genomic hybridization revealed comparable euploidy rates of 69.3% and 67.3%, respectively ( p > .05). DFI did not have an impact on the blastocyst euploidy rate in IVF cycles with egg donors.